Does Simultaneous Administration of Bivalent (Types 1 and 3) Oral Poliovirus Vaccine and Inactivated Poliovirus Vaccine Induce Mucosal Cross-immunity to Poliovirus Type 2?. (30th October 2018) - Resik, Sonia; Tejeda, Alina; Mach, Ondrej; Fonseca, Magile; Diaz, Manuel; Alemany, Nilda; Heng Hung, Lai; Aleman, Yoan; Mesa, Ileana; Garcia, Gloria; Sutter, Roland W
Abstract: Background: Inactivated poliovirus vaccine (IPV) alone does not induce mucosal immunity. However, it was hypothesized that administration of IPV together with bivalent (types 1+3) oral poliovirus vaccine (bOPV) may stimulate mucosal cross-immunity to poliovirus type 2 (PV2). Methods: Cuban infants were randomized to receive either one dose of IPV (Arm A); one dose of IPV with bOPV (Arm B) at about 6 months of age or no vaccine (Arm C). Subjects were challenged with one dose of trivalent OPV (tOPV); they were about 7 months old in arms A and B, and about 3 months old in arm C at a time of the tOPV challenge. Sera were collected before vaccination and 30 days after tOPV challenge and tested for presence of poliovirus neutralizing antibodies; stool samples were collected at days 0, 7, 14, 21 and 49 post-challenge and tested for presence of poliovirus. Results: We enrolled 333 children. Excretion of PV2 following tOPV challenge was highest on day 7 (75 [CI 95% = 65-82%], 68 [CI 95% = 58-75%] and 73 [CI 95% = 63-80%] for study arms A, B, and C respectively); excretion decreased with every subsequent stool sampling; no significant differences either in proportion of PV2 excretion or in its duration were observed between study arms. Conclusions: There was no reduction in excretion of PV2 after tOPV challenge in children who had received IPV with bOPV when compared to those who had received IPV alone or no vaccine. Polio eradication program cannot assume any PV2 mucosal response with the current polio immunization schedule. Clinical Trials Registration: The trial was registered with the Australian New Zealand Clinical Trials Registry and allocated trial number ACTRN12616000169448.